The COVID-19 Pandemic (Strains "Delta", "Omicron"): Particularities of Study on the Thematic Cycle "General Pharmacy Based on Pharmaceutical Law" - Shapovalova Вікторія; Shapovalov Валерій; Shapovalov Валентин; Osyntseva Аліна; Negretskii Сергій; Derkach Анатолій; Sichkarenko Олександр (Actual Problems of Medicine and Pharmacy, 2022)
The COVID-19 pandemic (Delta, Omicron strains) helped to optimize online work, which required the development of new skills in the Internet and additional workload on the teaching staff of the Department (individual work with students, interns in a convenient for their time and days off, etc.). The teaching staff and scientists of the Department of KhMAPE successfully conduct cycles using distance learning technologies and 98% of students are satisfied with the courses. The department actively cooperates with the teaching staff and scientists of LMI and other universities of Ukraine, CIS and EU countries. It was emphasized that the development and promotion of the national strategy of higher education based on world experience can increase the competitiveness of Ukrainian universities in the global education market and meet the needs of the national and global labor market.